A Versatile Planar Building Block with C2V Symmetry for High‐Performance Non‐Halogenated Solvent Processable Polymer Donors. Issue 16 (10th March 2022) - Wang, Hang; Lu, Hao; Chen, Ya‐Nan; Zhang, Andong; Liu, Yuqiang; Li, Dawei; Liu, Yahui; Xu, Xinjun; Bo, Zhishan
Abstract: Planar building block B2TCl with C2V symmetry configuration is designed to prepare polymer donors (PB2TCl‐ o and PB2TCl‐ i ) with good solubility in non‐halogenated solvents. When blended with BTP‐ec9‐4F, PB2TCl‐ o ‐based devices processed by 1, 2‐dimethylbenzene ( o ‐DMB) give a power conversion efficiency (PCE) of 15.10% with a V oc of 0.89 V, a J sc of 24.37 mA cm –2, and an fill factor of 69.69%. Semitransparent OSCs based on PB2TCl‐ o :BTP‐ec9‐4 can afford a PCE of 9.09% with an average visible transmittance (AVT) of 23.9% and an AT of 24.2%. B2TCl‐ o is also used as a third component to prepare random terpolymers PW1 and PW2. Using o ‐DMB as the processing solvent, PW1 and PW2‐based devices give improved PCEs of 16.26% and 17.19%, respectively, which are much higher than the parent polymers (PM6 and D18). This work provides a versatile building block B2TCl‐ o for the preparation of non‐halogen solvent processable high‐performance polymer donor materials. Abstract : Non‐halogenated solvent processable polymer donors are prepared using planar building block B2TCl‐ o with C2V symmetry. The device gives a power conversion efficiency (PCE) of 15.10% with 1, 2‐dimethylbeneze as processing solvent and the corresponding semitransparent device can afford a PCE of 9.09%. Terpolymers PW1 and PW2 with B2TCl‐ o as the third component can deliver higher PCEs of 16.26% and 17.19%, respectively.